Prevalence, awareness, treatment and control of arterial hypertension in Astana, Kazakhstan. A cross-sectional study - Supiyev, A.; Kossumov, A.; Utepova, L.; Nurgozhin, T.; Zhumadilov, Z.; Bobak, M. (Public Health, 2015)
Abstract ObjectiveVery little is known about prevalence of common cardiovascular risk factors in Central Asia. The aim of the study was to assess the prevalence, awareness, treatment and control of arterial hypertension, and factors associated with these indices in a population sample of Astana, the new capital city of Kazakhstan. DesignCross-sectional study of subjects registered in eight outpatient policlinics in Astana. MethodsA total of 497 adults (response rate 56%) aged 50–75 years randomly selected from registers of the policlinics were examined. Hypertension was defined as a mean systolic and/or diastolic blood pressure of ≥140/90 mm Hg and/or antihypertensive medication use during the last two weeks. Awareness and treatment were based on self-report. Hypertension control was defined as blood pressure <140/90 mm Hg among hypertensive subjects. ResultsThe overall prevalence of hypertension was 70%. Among hypertensive subjects, 91% were aware of their condition, 77% took antihypertensive medications, and 34% had blood pressure controlled (<140/90 mm Hg). The prevalence of hypertension and its awareness, treatment and control was more common in women, among persons aged 60 years or more and (except control) among those with high body mass index. None of several available socio-economic or lifestyle measures was associated with any of hypertension indices. ConclusionsThe levels of awareness, treatment and control of hypertension were higher than in most Eastern European and Central Asian populations with available data, most likely reflecting high education and large proportion of civil servants in the new capital city. However, even in this privileged population the rates of successful control of hypertension were modest.
Keywords: Arterial hypertension; Socio-economic factors; Central Asian countries